For king and country voices from the First World War - MacArthur, Brian (Little, Brown, 2008)
Far more than an anthology, this gripping collection of writings tells the story of World War I from the perspective of those who endured its horrors both home and abroad. From the men who served in Europe come accounts of fear, tedium, horror, and occasional joy, while those on the home front describe the pain of waiting for news of their loved ones. Along with selections from letters, diary entries, and memoirs, famous songs sung in the trenches as well as poems from soldiers and noted authors alike are also included. Together these documents create a seamless and movingly immediate narrative of one of the century's most infamous conflicts.